(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
Visual theater is an inter-disciplinary art form at the seam-line between performance and visual art. What is the role of puppets, masks and objects in visual theater? Can puppet-theater be regarded as an independent medium that is but a reduced, singular expression of visual theater? Is not all theater visual? In this paper Ophrat shall follow the puppet’s journey in the metaphorical space and time of theater, from mimetic and narrative functions to the values of matter, shape and medium: in other words – from the theater to the visual.